Artistic measures of poetic criticism in Kurdish literature (1970-1990) for example - Dilshad Ali Mohammed; Saeed Mohammed Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Literary criticism is a linguistic work at the highest level of linguistic thought, and in a literal sense literary criticism isa matter of writing on another written product. Above all, literary criticism is a critique of human attitudes in the end. The writing of literary criticism in all its methods is based on humanitarian attitudes and the critic may come in his general conclusions in a detailed and detailed reading. From this point of view, what is highlighted in this study is the criterion employed in poetry criticism and analysis in a perspicacious and scientific manner. Throughout the history of the Kurdish poetry, the poet has been regarded as a person with a message aiming to heal the wounds of society with his/her poems and reduce its aches, and contribute to the policy of the Kurdish nation. This book also shows what the critic criticizes via the methods of analysis and evaluation in his critique of poetry. The language of art and literature have always been the sources of the Kurdish language, while the expression and artistic images are the essence of the poet’s creativity, that is, those assets and poetic elements are the most important targets of this criticism method.